The Impact of Antimicrobial Stewardship Program on Injudicious Use of Cefuroxime - Arulappen, Ann L.; Danial, Monica; Haron, Norliza; Hau, Lim Choo; Khan, Amer Hayat (Frontiers in Pharmacology, 2021)
Antimicrobial stewardship (AMS) program promotes the judicious use of antimicrobials. Hence, this study was conducted to analyze the impact of stewardship towards the prescribing pattern of Injection Cefuroxime among the surgeons as perioperative antimicrobial prophylaxis (PAP). This study was conducted retrospectively in Malaysia. Various outcomes were measured which includes Cefuroxime usage, compliance to the guidelines, surgical site infections and also the cost savings. A total of 1601 patients were recruited into the study period. In terms of usage, the total defined daily dose (DDD) prior to the intervention was 202 DDD/100 procedures compared to post intervention which was 144 DDD/ 100 procedures (p<0.05). While the excessively long administration of PAP was reduced from 94.4 % to 30.3% (p< 0.001). Focusing on the compliance to the newly developed local guidelines, it has increased from 53% to 94.3% after the interventions were made (p<0.001) whereas the rate of surgical site infections dropped from 17.0% to 9.0%. Cost of antibiotic being used has significantly reduced after the study intervention (p=0.007). The quality of PAP directly impacts the antimicrobial usage, surgical site infections and the total cost involved. Thus, it is crucial to maintain the standard of PAP at all time in healthcare settings.